Thermodynamics of Manganese Adsorption on Some Soils - Arora, Harsh; Bhardwaj, S.S.; Sharma, B.D. (Asian Journal of Chemistry, 2010)
Adsorption reactions are of utmost importance to understand the availability of nutrients to the plants. The thermodynamic parameters (ΔGo, ΔHo and ΔSo) or the adsorption of manganese on six soils were calculated at two temperatures, i.e., 25 and 35°C. The adsorption data, fitted into the linear form of the Langmuir equation, made it possible to evaluate the adsorption maxima and binding energy. The values of ΔGo, ΔHo and ΔSo were found to be negative in all the soils indicating the exothermic and spontaneous nature of the adsorption reaction.